2004
DOI: 10.2307/4148991
|View full text |Cite
|
Sign up to set email alerts
|

Contraction Bias in Memorial Quantifying Judgment: Does It Come from a Stable Compressed Memory Representation or a Dynamic Adaptation Process?

Abstract: A common response bias in psychophysical judgments is regression toward the mean (overestimation of small and underestimation of large values, or the response contraction bias). The same bias is observed in magnitude estimation from memorized quantities. Participants estimated alphabetic interval distances between 2 letters for different levels of interletter distances. The underestimated and overestimated values and the point of least error changed, depending on the level of alphabetic distances judged; furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…We attribute a resultant narrowing of the response range as a progressive propensity to estimate values towards a value (mean, median or preferred), quantified as the level of minimum estimation error bias, due to the necessity of using memory to recall DR and allocating a given stimulus intensity within it. This phenomenon has been described previously as contraction bias (Jou et al 2004) and underlines the difficulty of recalling DR as well as relating present stimulus intensity with an accurately recalled DR (Baird 1997). …”
Section: Discussionmentioning
confidence: 59%
“…We attribute a resultant narrowing of the response range as a progressive propensity to estimate values towards a value (mean, median or preferred), quantified as the level of minimum estimation error bias, due to the necessity of using memory to recall DR and allocating a given stimulus intensity within it. This phenomenon has been described previously as contraction bias (Jou et al 2004) and underlines the difficulty of recalling DR as well as relating present stimulus intensity with an accurately recalled DR (Baird 1997). …”
Section: Discussionmentioning
confidence: 59%
“…For instance, Bradley and Vido (1984) showed that people underestimated spatial distance between two objects when they based their judgment on memory of the objects, whereas Wearden and Ferrara (1993) showed that people tended to underestimate a sample duration that they had memorized a few (1-16) seconds beforehand (see also Casasanto & Boroditsky, 2008). Second, the representations of time and other physical magnitudes are both susceptible to regression towards the mean (also known as the contraction bias, Poulton, 1979, or Vierordt's law, Gu & Meck, 2011, with overestimation for magnitudes under the mean and underestimation for magnitudes above the mean (Ashourian & Loewenstein, 2011;Jou et al, 2004;Tresilian, Mon-Williams, & Kelly, 1999). For example, Tresilian et al (1999) showed that, when asked to reproduce the distance of an object, people overreproduced distances for objects that were near but under-reproduced distances for objects that were further away, while Jazayeri and Shadlen (2010) similarly found that people respectively over-and under-reproduce short and long durations.…”
Section: Discussionmentioning
confidence: 99%
“…2 There is a natural tendency to shift the sensation in memory toward the middle of a scale of intensities; participants performing estimation tasks are not certain about the true values of the stimuli and therefore keep their estimates well within the boundaries (or ranges) of stimulus values. 3 The second reason arises from the observation that the results of previous studies demonstrate a high degree of subjectivity in preferred illuminances and that test participants' results are approximately equally distributed across the entire stimulus range (see, e.g. Figure 2 in Jusle´n et al 4 ).…”
Section: Introductionmentioning
confidence: 99%